Extended Programs Reactions from Member Institutions and from Established Programs. Final Report of the AACTE Task Force on Extended Programs - Monahan, William G.; American Association of Colleges for Teacher Education, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
Results of an open-ended, five-question inquiry sent to sample members of the American Association of Colleges for Teacher Education (AACTE) are presented and discussed. The questionnaire sought to probe into how AACTE members feel about the concept of an extended or five-year program for preparing prospective teachers. Questions concerned: (1) faculty discussion of and openness to extended programs; (2) reaction from the "field" to extended programs; (3) major problems foreseen; (4) respondent's individual point of view about extended programs; and (5) AACTE's position on extended programs. Results of the limited survey suggested that there are significant concerns and mixed views about the advisability of any aggressive advocacy on the part of AACTE in behalf of extended programs. A summary is presented of responses to the survey questions, and some interpretive comments are offered. Views from deans and/or directors of already established extended programs are also presented, with reference to questions and concerns that were raised by survey respondents. An analysis findings of the study is accompanied by a recommendation to AACTE on future efforts. (JD)
Educational level discussed: Higher Education.
Administrators.
Policymakers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Attitudes; Curriculum Development; Degrees (Academic); Higher Education; Internship Programs; Preservice Teacher Education; Program Development; Program Length; Schools of Education; Student Attitudes; Teacher Attitudes; Teacher Education Programs; Teacher Educators; Time Factors (Learning); Extended Degree Programs; American Association of Colleges for Teacher Educ; Reports, Research